Impeller Flow Field Laser Velocimeter Measurements - L. A. Brozowski; T. V. Ferguson; L. Rojas (International Journal of Rotating Machinery)
Development of Computational Fluid Dynamics (CFD) computer codes for complex turbomachinery affords a complete three-dimensional (3-D) flow field description. While significant improvements in CFD have been made due to improvements in computers, numerical algorithms, and physical modeling, a limited experimental database for pump CFD code validation exists.